SURFACE COMPLEXATION AND PRECIPITATE GEOMETRY FOR AQUEOUS ZN(II) SORPTION ON FERRIHYDRITE: II. XANES ANALYSIS AND SIMULATION - Waychunas G.A.; Fuller C.C.; Davis J.A.; Rehr J.J. (My University, 2003)
X-ray absorption near-edge spectroscopy (XANES) analysis of sorption complexes has the advantages of high sensitivity (10- to 20-fold greater than extended X-ray absorption fine structure [EXAFS] analysis) and relative ease and speed of data collection (because of the short k-space range). It is thus a potentially powerful tool for characterization of environmentally significant surface complexes and precipitates at very low surface coverages. However, quantitative analysis has been limited largely to “fingerprint” comparison with model spectra because of the difficulty of obtaining accurate multiple-scattering amplitudes for small clusters with high confidence.
Keywords: Ferrihydrite